La méningite « prise en grippe » ? - Oumy Thiongane (Anthropologie & Santé)
The control of public health issues in Niger requires obeying the requirements of the international institutions for health. While we might expect that such requirements are practical, they also construct the representation of epidemic risk. Through an ethnography of decision-making within a Nigerian and European expert committee during the onset of the AH1N1 influenza pandemic and the most important meningitis epidemic in Niger for over a decade, this paper highlights the differences between the representations of risk. It shows that different and conflicting logics govern the management of epidemic and that the most important issue concerns the availability of resources and their provision that allow the control of infectious diseases. This step depends strongly on how international institutions represent the risk. Moreover, this paper shows that the preparedness paradigm related to the meningitis epidemic is often faced with constructed contingencies.